Loneliness patterns and sleep problems after the initial outbreak of COVID-19: Findings from the Survey of Health, Aging and Retirement in Europe (SHARE). Issue 1 (2nd January 2023) - Shiovitz-Ezra, Sharon; Erlich, Bracha
ABSTRACT: The study addressed the relationship between loneliness and sleep deficits after the COVID-19 outbreak. We tested associations between patterns of loneliness before and after the outbreak [stable, improved, and worsened] and sleep quality outcomes: 1) having a sleep problem after the initial outbreak, and 2) change in sleep quality. Data were drawn from two data collection points in the Survey of Health, Aging and Retirement in Europe (Wave 8 and the SHARE-COVID telephone survey). The sample included 35, 878 respondents from 27 countries who participated in both of the data collection points and had full information on the relevant variables. Having a sleep problem was measured on a single-item indicator. Five loneliness patterns were identified. These included three stable patterns: (1) 'little or no loneliness' (2) 'mild persistent loneliness, ' (3) 'intense persistent loneliness, ' and two patterns of change in loneliness status after the outbreak: (4) 'improved' and (5) 'worsened.' In the adjusted models, all of the loneliness patterns were associated with having a sleep problem after the initial outbreak, compared to those with a stable pattern of no loneliness. Moreover, intensive persistent loneliness almost doubled the risk of experiencing a sleep problem after the outbreak and was a robust predictor of a negative change in sleep quality. Among older adults, intense loneliness experienced both before and after the initial outbreak of COVID-19 emerged as the most deleterious loneliness status in terms of post-outbreak sleep quality.